Covalent Immobilization of alpha-Amylase onto UV-Curable Coating - KAHRAMAN, MEMET VEZİR (WILEY, 2009)
A UV-curable N-(4-sodiumsulfophenyl)maleimide monomer was synthesized, and its potential for enzyme binding was investigated. The bromine, which is used to activate the synthesized monomer for covalent attachments, has the advantage of giving reaction with the surface groups of enzyme under very mild conditions (0 degrees C, 30 min). In this procedure, sulfonyl bromide pendant monomer reacted with amino groups of the protein to form sulfonamide bonds. Polymeric support was prepaped by UV-curing technique. The water adsorption value was found to be less than 1%. The enzyme-bounding yield was found to be 68.18 +/- 4.20 mg/g monomer. The maximum activity was observed at pH 6.5. Immobilization did not change the pH-dependency of the enzyme activity. It was found that the optimum temperature for the free enzyme was similar to 30 degrees C, whereas it shifted to nearly 50 degrees C for the immobilized enzyme. Free enzyme lost its activity completely within 15 days. Immobilized enzyme lost only 30% of its activity in 30 days. (C) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 114: 3716-3722, 2009
Keywords: alpha-amylase; covalent immobilization; UV curing coating; sulfon amide; CARBONATE; MEMBRANE; TOOL